Bioinspired deposition of TiO2 thin films induced by hydrophobins - Santhiya, D (Langmuir : the ACS journal of surfaces and colloids, 2010)
The deposition of ceramic thin films from aqueous solutions at low temperature using biopolymers as templates has attracted much attention due to economic and environmental benefits. Titanium dioxide is one of the most attractive functional materials and shows a wide range of applications across vastly different areas because of its unique chemical, optical, and electrical properties. In the present work, we deposited smooth, nanocrystalline titania thin films by an aqueous deposition method on surface active and amphipathic proteins of fungal origin called hydrophobins. Initially, the hydrophobin molecules were self-assembled on a silicon substrate and characterized by angle-resolved X-ray photoelectron spectroscopy (AR-XPS), atomic force microscopy (AFM) and surface potential measurements. Thin films of titanium dioxide were deposited on the surface of hydrophobin self-assembled monolayers from aqueous titanium(IV) bis(ammonium lactate) dihydroxide solution at near-ambient conditions. The microstructure of the as-deposited films was analyzed by AFM, scanning and transmission electron microscopy, which revealed the presence of nanocrystals. The titania films were also characterized using AR-XPS and Fourier transform infrared spectroscopic (FTIR) techniques. Appropriate mechanisms involved in film deposition are suggested. Additionally, nanoindentation tests on as deposited titania films showed their high resistance against mechanical stress